Tingkat Kepuasaan Pelayanan Kefarmasian Pada Pasien Rawat Jalan di RSUD dr. Murjani Sampit - Agusthin, Ishae Tri; Pratomo, Guntur Satrio; Ardhany, Syahrida Dian (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Pharmaceutical services in hospitals play an essential role in supporting the quality of healthcare services and influencing patient satisfaction levels. This study aimed to evaluate patient satisfaction with pharmaceutical services at the outpatient pharmacy of RSUD Dr. Murjani Sampit based on five satisfaction dimensions: reliability, responsiveness, empathy, tangibles, and assurance. This study used a quantitative method with a descriptive approach. Data were collected through a validated questionnaire survey. Patient satisfaction was measured using a Likert scale ranging from one to five points. The results show that pharmaceutical services at RSUD Dr. Murjani have a good level of satisfaction across all measured dimensions. The reliability dimension scored 78.67%, reflecting the accuracy and clarity of information provided by pharmacists. The responsiveness dimension scored 79.79%, indicating fast service despite resource limitations. The empathy dimension scored 78.97%, demonstrating the staff’s attentiveness to patient needs. The tangibles dimension scored 77.95%, describing facility comfort, though some improvements are needed. The assurance dimension scored 75.1%, indicating good medication availability. Overall, pharmaceutical services at RSUD Dr. Murjani meet good quality standards and provide patient satisfaction, although some aspects can be improved to enhance the overall patient experience.